Gunshot Wound Simulation Case - Aaron Rubin; Raymond Ten Eyck (Association of American Medical Colleges, 2012)
Abstract A male in his upper 20's sustains a single gunshot wound in the abdominal left upper quadrant/costal margin area of his lower chest. He is stable on the scene and transported via EMS to the emergency department. Upon arrival in the ED the patient becomes hypotensive and less responsive. The patient requires intubation and aggressive fluid resuscitation. He is found to have a left sided tension pneumothorax requiring needle decompression and placement of a chest tube. He is initially responsive to fluid resuscitation but requires emergent infusion of blood due to hypotension despite fluid resuscitation. Prior to initial submission this simulation was run with multiple residents and a 4th year medical student and was found to be effective by both teaching facility and residents/student in covering major learning points in gunshot wound stabilization and treatment. Since initial submission and before publication this simulation case was used to train interdisciplinary teams consisting of a total of 140 experienced EM physicians, nurses, nurses aids, respiratory therapists and technicians. The participants rated the learning experience as a 3.9 on a 4 point Likert scale.